Toxoplasmosis in military personnel involved in jungle operations (2012)
Tropical diseases, mainly leishmaniasis and malaria, increased among Colombian military personnel due to intensive operations in the jungle in the last ten years; as a result the Colombian army developed important preventive strategies for malaria and leishmaniasis. However, no knowledge exists about toxoplasmosis, an emergent disease in military personnel. We compared the prevalence of IgG anti-Toxoplasma antibodies by ELISA and of parasitaemia by a real time PCR assay, in 500 professional soldiers that operated in the jungle with a group of 501 soldiers working in an urban zone (Bogotá). We found that the prevalence was significantly different between both groups of soldiers (80% in soldiers operating in jungle vs. 45% in urban soldiers, adjusted OR 11.4; CI 95%: 3.8–34; p < 0.0001). All soldiers operating in the jungle drink unboiled and chlorine untreated lake or river water. In urban soldiers, these risk factors along with eating wild animal meat or eating tigrillo (little spotted cat) were significantly associated with a higher prevalence. Characteristic toxoplasmic choriorretinal lesions were found in 4 soldiers that operated in the jungle (0.8%) and in one urban soldier (0.19%). All soldiers before being deployed in jungle operations should be tested for Toxoplasma antibodies and to receive adequate health information about the routine use of personnel filters to purify their water for consumption.